If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 11 = 5 + 3y Solving 11 = 5 + 3y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-3y' to each side of the equation. 11 + -3y = 5 + 3y + -3y Combine like terms: 3y + -3y = 0 11 + -3y = 5 + 0 11 + -3y = 5 Add '-11' to each side of the equation. 11 + -11 + -3y = 5 + -11 Combine like terms: 11 + -11 = 0 0 + -3y = 5 + -11 -3y = 5 + -11 Combine like terms: 5 + -11 = -6 -3y = -6 Divide each side by '-3'. y = 2 Simplifying y = 2
| 5x+4=7x+4 | | 80=y | | 11=19-2b | | (2x-80)=x | | -2x-28=67-7x | | (5a-3)(5a-3)= | | 2x/x-9-x/2(x-9)= | | 3(2x-5)-(x+3)=(2x+1)+4 | | 7=10-3u | | 5a-2=3a+4 | | 2(x-4)+12=x-4(6+2x)+9x | | 12×-1/3 | | 13=10 | | 3log(2)x=28 | | -53/4-31/2= | | 4x-40=13-6x+3 | | 2y-10x=10 | | 3.50x=10.50 | | 3x^2+10=100 | | 2x+7=15+4x | | 2x+12+9=x+3 | | 6x+5+9x-10+80+90=360 | | X+6=-8x+5 | | (x^2+0.8)(x^2+0.8)= | | 3x-29=17-5x | | 18=9+3h | | 7tanx+2=9 | | 3y+6-2=8-2y | | 7/3*8/6 | | -4/7y16 | | 12=15-3p | | 2(x-4)+12=x-4(6+2x)+9 |